IMPLEMENTASI PERATURAN KEPALA DESA TENTANG BANTUAN LANGSUNG TUNAI (BLT) DANA DESA AKIBAT DAMPAK PANDEMI DI KABUPATEN GARUT PROVINSI JAWA BARAT - Arwanto Harimas Ginting; Wira Abdillah Bintang (Jurnal Kebijakan Pemerintahan, 2021)
This research aims to review the implementation of the Village Cash Direct Assistance policy through village head regulations in poverty reduction since the Covid-19 pandemic in Keresek Village of Cibatu Subdistrict, Garut Regency. The Village Cash Direct Assistance (BLT DD) is one of the government's initiatives in providing subsidies to Indonesians in need. Assistance is offered to address the problems caused by the prolonged Covid-19 pandemic in Indonesia and worldwide. The Covid-19 pandemic does not only interfere with health that results in death. Pandemics force various activities to be stopped so that the impact is widespread, increasing the number of unemployment, hunger, poverty, etc. For this reason, the government provides funds to the community to suppress the increasing problem. Implementation of village-level policies using village head regulations is still rare. This research used qualitative methods using Edward III's policy theory of communication, resources, disposition, and bureaucratic structure. Data sources were obtained through interviews and documentation—data analysis by presenting data, reducing data, and withdrawing conclusions. The research result shows that the implementation of Village Cash Direct Assistance in Keresek Village based on Edward III's theory has been implemented judging from the absence of complaints ranging from the data collection process to distribution to recipients under Operational Standard Procedure (OSP). This research will inform the implementation of policies at the village level made by the village government. Keywords: Village Fund, Policy, Policy Implementation.